The impact of user addiction on continuance intention to use streaming platforms: incorporating expectation confirmation model and personality traits - Sae-tae, Kittiporn; Ling, Jinzhu; Wang, Qian (Frontiers in Communication, 2024)
The widespread use of the Internet has transformed communication, including listening to music and watching movies. With the development of new technologies, consumers now have more options for viewing new media across many platforms and devices. Consumers now have more options for watching new material across many platforms and devices via OTT (Over-the-Top) streaming platforms. Future trends in consumer behavior will significantly increase competition for the digital media business, particularly in the digital video and music sectors. This article aims to understand better Thai streaming service users, where the country’s digital infrastructure has been developing. By examining their heavy viewing addiction, intention to continue using the expectation confirmation model, personality traits, and implementation of the 7Ps in marketing. An online questionnaire-based survey of Thai respondents was used to evaluate the proposed models empirically. The study used path analysis and a Structural Equation Model (SEM) to investigate how continuance intention toward streaming services is affected by other endogenous variables in Thailand. The empirical results found that the user’s satisfaction and addiction of users to heavy viewing were found to be key factors influencing the intention to continue using streaming services in the Thai environment. Likewise, the study confirms the importance of the Big Five personality traits theory in impacting the behavior of streaming service consumers. Introverted persons may perceive streaming services as more useful and enjoyable. The findings deepened our understanding of Thai streaming consumer behavior and offered more insight into market trends for streaming services.